2020
DOI: 10.1038/s41598-020-70403-5
|View full text |Cite
|
Sign up to set email alerts
|

The influence of hydrodynamic exposure on carbon storage and nutrient retention in eelgrass (Zostera marina L.) meadows on the Swedish Skagerrak coast

Abstract: Cold-temperate seagrass (Zostera marina) meadows provide several important ecosystem services, including trapping and storage of sedimentary organic carbon and nutrients. However, seagrass meadows are rapidly decreasing worldwide and there is a pressing need for protective management of the meadows and the organic matter sinks they create. Their carbon and nutrient storage potential must be properly evaluated, both at present situation and under future climate change impacts. In this study, we assessed the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 79 publications
1
19
0
Order By: Relevance
“…Sediment density seems also to have a significant role for C org levels in seagrass habitats, as shown by the models in this study and by earlier studies elsewhere (e.g. Avnimelech et al 2001;Dahl et al 2016bDahl et al , 2020aRöhr et al 2018). High C org content is generally associated with low sediment density since organic material has a lower weight compared to minerogenic particles (Winterwerp and van Kesteren 2004) and a higher water content (Avnimelech et al 2001).…”
Section: Discussionsupporting
confidence: 80%
“…Sediment density seems also to have a significant role for C org levels in seagrass habitats, as shown by the models in this study and by earlier studies elsewhere (e.g. Avnimelech et al 2001;Dahl et al 2016bDahl et al , 2020aRöhr et al 2018). High C org content is generally associated with low sediment density since organic material has a lower weight compared to minerogenic particles (Winterwerp and van Kesteren 2004) and a higher water content (Avnimelech et al 2001).…”
Section: Discussionsupporting
confidence: 80%
“…Three sedimentary variables (mud content, sediment density, and degree of sediment sorting), and two environmental variables (water depth and salinity) explained over 62% of this variation in the study by Röhr et al (2018). Earlier studies in other regions with Z. marina meadows (Dahl et al, 2016;Dahl et al, 2020;Miyajima et al, 2015;Röhr et al, 2016) or other species of seagrass (Macreadie et al, 2013Serrano et al, 2016 have also indicated that sediment characteristics, specifically the sediment grain size distribution and sediment density, appear to be the most important predictors for seagrass carbon stocks. However, the seagrass organic carbon stocks here were not related to the sediment dry bulk density (top 5cm or 10cm).…”
Section: Discussionmentioning
confidence: 77%
“…Grain size distribution might also change due to overgrazing, as smaller particles are more volatile than those of larger sizes (Rose et al 1999). Hydrodynamic exposure level is highly influencing the sedimentation process and is an important factor affecting the carbon storage potential in seagrass meadows (Samper‐Villarreal et al 2016; Prentice et al 2019; Santos et al 2019; Dahl et al 2020). The attenuation of the water flow by the seagrass canopy, which allows the sediment and sedimentary carbon to accumulate (Gacia and Duarte 2001), will be disrupted during an overgrazing event as the shoot biomass is being lost (James et al 2020).…”
Section: Resultsmentioning
confidence: 99%